Immunopathogenesis of feline immunodeficiency virus infection in the fetal and neonatal cat - Kolenda-Roberts, Holly M. (2007)
The global incidence of pediatric HIV infection is estimated at 2.3 million children, most acquiring the infection from their mothers in utero, peripartum, or postpartum. Pediatric HIV infection typically causes a rapidly progressive disease when compared with adult infection, due in part to the profound susceptibility of the neonatal thymus to productive infection or degenerative changes. Failed production of naïve T-lymphocytes further limits the success of antiviral therapy to restore immunologic function. In this review, we explore the use of feline immunodeficiency virus (FIV) infection of domestic cats as an animal model for pediatric HIV infection. Cats infected with FIV represent the smallest host of a naturally occurring lentivirus, and the immunodeficiency syndrome elicited by FIV infection is similar to that of HIV-AIDS. The feline-FIV model uniquely reproduces several key aspects of immunosuppressive lentivirus infection of the thymus, allowing investigators to define viral determinants of pathogenicity, influence of host age on disease outcome, and therapeutic strategies to restore thymus function.